Analisis Faktor Keberlanjutan Pemanfaatan Chatbot Akademik pada Perguruan Tinggi - Nabarian, Tifanny; Ali Akbar (AI Society & STMIK Indonesia, 2025)
This study examines the factors influencing the continued use of chatbot use as an academic information platform and identifies key factors contributing to its utilization. Data were collected through interviews and questionnaires, then analyse using the PLS-SEM method with Adanco software. The results show that System Quality has the strongest influence on Perceived Ease of Use (0.5326), which subsequently has a positive impact on Continued Use (0.4816). E-Service Quality also significantly affects User Satisfaction (0.3516). However, Information Quality and Perceived Usefulness show low influence on *User Satisfaction (0.2234) and Continued Use (0.1354), respectively. In terms of reliability, the constructs Continued Use (0.9147), E-Service Quality (0.9203), and Perceived Usefulness (0.8866) demonstrate strong measurement consistency, while System Quality (0.6363) requires improvement. The Q² analysis indicates that the model has good predictive relevance, with Continued Use (0.4349) emerging as the dominant variable